The free uses of copyrighted works in Cape Verdean law - notes on a brief essay on its scope and foundation - MONIZ, José Maria (Revista Jurídica Portucalense, 2024)
The scope of this essay is to scrutinize the limitations to which copyright is subject in the Capeverdean legal system. For this purpose, we will analyze, at first, the copyright protection regime and the systems aimed at limiting the rights granted to the author. Subsequently, we will study the system adopted at internal level, and the range of limitations formulated by the ordinary legislator. The result of this essay is, among others, that the domestic legal framework classifies free uses taxatively and is highly protectionist of copyright, for which we argue for some flexibilization